TEKNOLOGI SEBAGAI INSTRUMEN POLITIK KEKUATAN BESAR: SEBUAH OVERVIEW TERHADAP PERANG TEKNOLOGI AS-CHINA - Alfian, Muhammad Faizal; Hudaya, Maula; Anggraheni, Palupi; Zuliyan, Muhammad Arief (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2025)
Technology competition between the United States and China started to growth significantly at the international level. The United States has implemented highly restrictive policies toward Chinese technology accomplishments. In retaliation, China has responded to US sanctions and limited its access to advanced semiconductors by emphasizing independence and making investments in its own semiconductor manufacturing sector. With both countries imposing tariffs and restrictions on technology companies, the dispute has escalated into a full-fledged technology war. A series of policies have pushed the two countries further apart and towards a technology war. By using power analysis as the main conceptual framework, this research focuses on examining why technology is a fundamental aspect of the US-China great power rivalry. As a concept of power growth, technology accomplishment should not only be positioned as a medium to increase economic interests but also a tool to improve military capabilities and national security. The shifting from technological competition to technological supremacy for the purpose of political domination and influence is inevitable. Thus, technological war and power struggle also have the potential consequences of prolonged conflict and could transform the global economic and political landscape. Key words: Technological War, Great Power Politics, US-China Rivarly